AL- TAFSÎR AL-' ILMÎ ANTARA PENGAKUAN DAN PENOLAKAN - Udi Yuliarto (Khatulistiwa, 2011)
Eighteenth century AD, is the development of science in Europe, at this time there are many books which were translated into European languages such as physics, chemistry and medicine. The knowledge development had affects the separation between science and religion of European society at that time. The scientists were discovered some theories of knowledge that always contrary to the opinion of the church so that not a few of them must die on the gallows. Religious books in they opinion only contain superstition and illogical doctrine that makes them imprisoned in ignorance. This development brings a huge impact on the Islamic world and Muslims. The Muslims scholars are required to maintain the authenticity of Islamic religious teachings that are not in conflict with science. They develop scientific interpretation (tafsîr 'ilmy) in order to prove the miracles of the Koran. So that Islam can prove and answer all the challenges of the times. The interpretation of Koran by using the experimental sciences has produced many books of scientific interpretation (tafsîr 'ilmy) and became an important reference. However, did not rule out this development led to the shift of functions of the Koran as a guidance holy book to the book of knowledge by some mufassir which interpreted influenced by foreign cultures, so that Koran interpretation was leaning on ra'yi (pure opinion) and exit from the rules of correct interpretation (tafsîr). This incident makes Muslims scholars in Egypt and Syria encouraged to determine the position of the correct scientific interpretation (tafsîr 'ilmy) of the incorrect scientific interpretations (tafsîr 'ilmy).